2009
DOI: 10.1002/ajmg.a.32760
|View full text |Cite
|
Sign up to set email alerts
|

Differential PERP regulation by TP63 mutants provides insight into AEC pathogenesis

Abstract: Ankyloblepharon Ectodermal Dysplasia and Cleft Lip/Palate (AEC) or Hay-Wells Syndrome is an autosomal dominant disorder characterized by a variety of phenotypes in ectodermal derivatives, including severe skin erosions, ankyloblepharon, coarse and wiry hair, scalp dermatitis, and dystrophic nails. AEC is caused by mutations in the gene encoding the TP63 transcription factor, specifically in the Sterile Alpha Motif (SAM) domain. The exact mechanism, however, by which these specific TP63 mutations lead to the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 22 publications
3
24
0
Order By: Relevance
“…5B) (18). The steady-state level of TAp63␣ AEC mutant proteins was lower than that of wild-type TAp63␣ as published previously (18) and is, at least in part, due to decreased stability of the AEC mutant proteins (data not shown). In contrast, loss of the OD, either by truncation or point mutation (I378P), significantly abrogates reporter induction (Fig.…”
Section: Satb2 Differentially Regulates Human Disease-associated Aec supporting
confidence: 82%
See 3 more Smart Citations
“…5B) (18). The steady-state level of TAp63␣ AEC mutant proteins was lower than that of wild-type TAp63␣ as published previously (18) and is, at least in part, due to decreased stability of the AEC mutant proteins (data not shown). In contrast, loss of the OD, either by truncation or point mutation (I378P), significantly abrogates reporter induction (Fig.…”
Section: Satb2 Differentially Regulates Human Disease-associated Aec supporting
confidence: 82%
“…2E). An essential gene regulated by p63 during ectoderm development is perp (10,18). ChIP analysis showed that overexpressed TA and ⌬Np63␣ (Fig.…”
Section: B-d)mentioning
confidence: 98%
See 2 more Smart Citations
“…Since Perp is strongly reduced in p63 null embryos and in p63-depleted keratinocytes and its absence predisposes to ectodermal dysplasia and skin blistering in mice (ADD (Ihrie et al 2005, its expression was tested in skin biopsies from AEC patients (Beaudry et al 2009); however, only a limited subset of AEC patients showed reduced PERP. This finding, in association to the evidence that the phenotype of Perp null mice is milder compared to the skin phenotype of p63 null mice, suggests that PERP is likely to contribute to the complex pathogenesis of AEC syndrome but is unlikely to be the affected gene mainly responsible for the disease.…”
Section: P63 and Desmosomesmentioning
confidence: 99%